Horkovodní kotel na biomasu menších výkonů - Fojtl, Martin (Vysoké učení technické v Brně. Fakulta strojního inženýrství, 2022)
Diplomová práce se zabývá návrhem horkovodního kotle na biomasu. Požadavky na ohřátou vodu jsou 130 °C a 20 bar. V práci se postupně vypočítá stechiometrie a tepelná bilance kotle ze zvoleného paliva. Tímto palivem je dřevní štěpka. Poté následuje výpočet spalovací komory a teplosměnných ploch. Na závěr jsou vypočítány ztráty na straně vody i ztráty na straně spalin. Součástí práce je výkres kotle, který je k nalezení v příloze práce.

This master’s thesis deals with design of grate hot water boiler. Requirements for hot water are a temperature of 130 °C, and pressure of 20 bar. In this thesis stoichiometric calculations and heat loss based on chosen fuel are presented. The chosen fuel is wood chips. Next, calculations of the combustion chamber, and heat exchangers are included. In the end pressure losses of water and exhaust gases are calculated. A part of this thesis is also a technical drawing documentation, which can be found in the attachment.
Grate Biomass Boiler
Keywords: Horkovodní kotel; spalovací komora; ekonomizér; tepelné ztráty; biomasa; Hot water boiler; combustion chamber; economiser; thermal losses; biomass